Experimental Study on the Performance of Basalt Fiber Modified Pervious Concrete Based on Entropy Method - Wenhua Wang; Xiaojun Cheng; Jinzhong Zhu; Da Jiang; Hongliang Sun; Siyu Liu (Advances in Materials Science and Engineering)
In order to solve the problem the permeability coefficient and strength of pervious concrete pavement are difficult to coordinate. In this paper, the basalt fiber was incorporated into pervious concrete, and the single factor control variable method was used to carry out the test of basalt fiber modified pervious concrete, and combined with the microstructure image, the influence law of different diameters, lengths, and dosages of basalt fibers on mechanical properties and pervious properties of pervious concrete were studied. The optimal incorporation index of basalt fiber was determined by a new analysis method—the entropy method. Finally, it is concluded that basalt fiber can improve the mechanical and pervious properties of pervious concrete by changing the internal structure of pervious concrete. In addition, when the diameter of basalt fiber increases from 14 μm to 20 μm, the compressive strength of pervious concrete decreases by 17.79%. The splitting tensile strength showed a trend of increasing to decreasing. The porosity and water permeability increased by 2.55% and 48.66%, respectively. When the basalt fiber length increases from 12 mm to 24 mm, the compressive strength of pervious concrete increases by 20.54%, and the splitting tensile strength increases first and then decreases. The porosity and water permeability increased by 6.40% and 57.68%, respectively. When the content of basalt fiber increases from 2 kg/m3 to 6 kg/m3, the compressive strength of pervious concrete decreases by 16.25%. The splitting tensile strength increases by 23.72%. The porosity and permeability decreased by 7.75% and 39.36%, respectively. Finally, the entropy method is used to comprehensively analyze the optimum incorporation indexes of basalt fiber, which can achieve the optimal mechanical properties and water permeability at the same time with, 20 μm in diameter, 24 mm in length, and 2 kg/m3 in dosage, and it provides a reference value for the popularization and application of basalt fiber pervious concrete in practical engineering.